(NHC-olefin)-nickel(0) nanoparticles as catalysts for the (Z)-selective semi-hydrogenation of alkynes and ynamides. Issue 11 (20th January 2023) - Avello, Marta G.; Golling, Stéphane; Truong-Phuoc, Lai; Vidal, Loïc; Romero, Thierry; Papaefthimiou, Vasiliki; Gruber, Nathalie; Chetcuti, Michael J.; Leroux, Frédéric R.; Donnard, Morgan; Ritleng, Vincent; Pham-Huu, Cuong; et al.
Abstract : Nickel(0)-NHC nanoparticles bearing cinnamyl moieties catalyse effectively ( Z )-selective semi-hydrogenations. Abstract : Nickel(0) nanoparticles coordinated to NHC ligands bearing N-coordinated cinnamyl moieties were readily prepared by reduction of a [NiCpBr(NHC-cinnamyl)] complex with methyl magnesium bromide. The combination of a strong σ-donor NHC ligand with a π-coordinating appended cinnamyl moiety likely prevents nickel(0) nanoparticle aggregation to larger inactive species, and allows the effective and ( Z )-selective semi-hydrogenation of alkynes and ynamides.